2021
DOI: 10.1002/solr.202100663
|View full text |Cite
|
Sign up to set email alerts
|

NiOx‐Seeded Self‐Assembled Monolayers as Highly Hole‐Selective Passivating Contacts for Efficient Inverted Perovskite Solar Cells

Abstract: Self‐assembled monolayers (SAMs) have emerged as effective carrier transport layers in perovskite (PVK) solar cells because of their unique ability to manipulate interfacial property, as well as simple processing and scalable fabrication. However, the defects and pinholes derived from their sensitive adsorption process inevitably deteriorate the final device performance. Herein, a sputtered nickel oxide (NiOx) interlayer is used as a seed layer to promote the adsorption of the [2‐(3,6‐dimethoxy‐9H‐carbazol‐9‐y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
96
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 41 publications
(43 reference statements)
5
96
0
Order By: Relevance
“…The result shows that NiO x passivates the ITO and prevents direct contact between perovskite and ITO, which contributes to improving the PCE. 50 Herein, we developed a similar strategy using sp-NiO x by coating MeO-2PACz on top of sp-NiO x to study the surface defect of NiO x and perovskite interfaces using different analytical techniques with the commonly used perovskite methylammonium lead iodide (MAPbI3). Despite these remarkable contributions, the application of MeO-2PACz, by modulating the crystal contact or layer between NiO x /perovskite, needs more investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result shows that NiO x passivates the ITO and prevents direct contact between perovskite and ITO, which contributes to improving the PCE. 50 Herein, we developed a similar strategy using sp-NiO x by coating MeO-2PACz on top of sp-NiO x to study the surface defect of NiO x and perovskite interfaces using different analytical techniques with the commonly used perovskite methylammonium lead iodide (MAPbI3). Despite these remarkable contributions, the application of MeO-2PACz, by modulating the crystal contact or layer between NiO x /perovskite, needs more investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Lastly, Sun et al developed a method to enhance the interaction between MeO-2PACz and ITO using a sputtered NiOx layer with triple-cation perovskite devices. The result shows that NiO x passivates the ITO and prevents direct contact between perovskite and ITO, which contributes to improving the PCE . Herein, we developed a similar strategy using sp-NiO x by coating MeO-2PACz on top of sp-NiO x to study the surface defect of NiO x and perovskite interfaces using different analytical techniques with the commonly used perovskite methylammonium lead iodide (MAPbI3).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of UPS, EDS and XPS, it can be speculated that ultrathin 2PACz self-assembles on the surface of NiO x film as exhibited in Figure 2c, tuning the characteristic of NiO x tremendously. [30] The contact angles of water on the surface of NiO x films with or without the modification layer displaying in Figure 2d,e have a great change, confirming 2PACz influences the hydrophilic property of NiO x tremendously. The inferior hydrophilic property of 2PACz compared with NiO x makes perovskite only nucleate on some places of the 2PACz surface, thus the perovskite can grow with compact grain.…”
Section: Resultsmentioning
confidence: 70%
“…Based on the results of UPS, EDS and XPS, it can be speculated that ultrathin 2PACz self‐assembles on the surface of NiO x film as exhibited in Figure 2c, tuning the characteristic of NiO x tremendously. [ 30 ]…”
Section: Resultsmentioning
confidence: 99%
“…Record e ciencies for both single junction and tandem solar cells have been recently achieved by coating the transparent oxide substrates with these molecular monolayers. [24][25][26] It has also been reported that perovskite layers deposited on SAM-treated substrates are resilient toward halide segregation. [24] We wanted to explore the stability and performance of the monolayer-based device stack with both wide and narrow gap absorbers.…”
Section: Introductionmentioning
confidence: 99%